2015
DOI: 10.1002/pds.3783
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection using change point analysis in postmarket surveillance

Abstract: PurposeSignal detection methods have been used extensively in postmarket surveillance to identify elevated risks of adverse events associated with medical products (drugs, vaccines, and devices). However, current popular disproportionality methods ignore useful information such as trends when the data are aggregated over time for signal detection.MethodsIn this paper, we applied change point analysis (CPA) to trend analysis of medical products in a spontaneous adverse event reporting system. CPA was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The same results were obtained with data from BNPV. Z. Xu et al found that change points in the count of report may be related to some issues like extended indication for use for devices. Similarly, we found that the increase in the number of reports related to benfluorex and ADRs may be due to the marketing suspension of this drug in November 2009.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The same results were obtained with data from BNPV. Z. Xu et al found that change points in the count of report may be related to some issues like extended indication for use for devices. Similarly, we found that the increase in the number of reports related to benfluorex and ADRs may be due to the marketing suspension of this drug in November 2009.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with change in mean, this approach is less sensitive to detect changes in safety data. 6 In the method elaboration phase, the CPA method was applied on the count of reports per month and the monthly PRR-. We defined trends of segments between detected change points, especially trends of measures after the moment that each couple was defined as a SDR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations